Use of heteroaromatic spacers in isoindigo-benzothiadiazole polymers for ambipolar charge transport. Issue 40 (9th July 2014) - Kim, Gyoungsik; Han, A-Reum; Lee, Hae Rang; Oh, Joon Hak; Yang, Changduk
Abstract : Not only do we report two new polymers (PIIG-DTBT andPIIG-DSeBT ) involving isoindigo and benzothiadiazole blocks constructed with thiophene and selenophene spacers, but also explore the optical, electrochemical, and charge-transport properties. Abstract : Inspired by the outstanding charge-transport characteristics of poly(isoindigo- alt -benzothiadiazole) (PIIG-BT) in our previous study, herein we present two new polymers (PIIG-DTBT andPIIG-DSeBT ) involving IIG and BT blocks constructed using five-membered heteroaromatic spacers such as thiophene (T) and selenophene (Se) and investigate the effects of the spacer groups on the optical, electrochemical, and charge-transport properties. As a consequence of the red-shifts induced by the more extended conjugation and enhanced intramolecular charge transfer (ICT), bothPIIG-DTBT andPIIG-DSeBT show smaller bandgaps compared to PIIG-BT. Interestingly, the LUMO energy levels (−3.57 eV) for the two polymers are the same, but the HOMO levels (−5.39 and −5.26 eV forPIIG-DTBT andPIIG-DSeBT, respectively) clearly vary as a function of the structural modification of the spacers. In addition to the changes in their optical properties and energy levels induced by the incorporation of the spacers, ambipolar charge transport behaviors with hole and electron mobilities of up to 7.8 × 10 −2 and 3.4 × 10 −2 cm 2 V −1 s −1, respectively, are observed forPIIG-DTBT films with highly ordered lamellar packing. This represents the second example of IIG-based polymers exhibiting ambipolar charge transport in OFETs reported to date.